Pengaruh Permainan Media Globe of Land And Water Terhadap Pengenalan Konsep Geografi Anak - Khalawati, Finahari Nur; Sagala, Anita Chandra Dewi; Karmila, Mila; Khasanah, Ismatul; Kusumaningtyas, Nila; Prasetyo, Agung (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
This study was motivated by children's low interest in understanding geography concepts such as cardinal directions, location and place. This study aims to determine whether the use of Globe of Land and Water learning media can improve the understanding of children aged 5-6 years on the concept of geography. This study uses a quantitative approach in the form of a pre-experimental method with an Intact-Group Comparision design. Data were collected through observation sheets used to observe performance and learning activities in children aged 5-6 years as many as 36 children conducted for approximately one week, documentation was carried out using anecdotal notes, taking pictures and videos to find out the activities of children and assessment using a scale scoring of children's understanding of geography concepts. The t-test results obtained a 2 tailed Significant value of 0.001 <0.05 as the decision making in the Independent Sample T-Test test if H0 is rejected then Ha is accepted, then children who use the Globe of Land and Water media have a significant increase in understanding of geography concepts compared to the control group. This proves that the use of the media is effective in helping children understand abstract geography concepts. The contribution of this study is that learning by using the globe of land and water game media can be implemented as a variation in the teaching and learning process, especially to improve children's understanding of geography concepts.